Evaluating the Feasibility of Developing National Outcomes Data Bases to Assist Patients with Making Treatment Decisions - Damberg, Cheryl L. (RAND Corporation, 2003)
This report examines issues surrounding the establishment of a national patient outcomes database that would be used by patients and providers to make more informed treatment decisions. It focuses on prostate cancer and surgery for osteoarthritis. The authors conclude that such longitudinal databases would be both desirable and feasible but would require substantial resources.